Optimizing biochar for carbon sequestration: a synergistic approach using machine learning and natural language processing - Jiayi Li; Yixuan Chen; Chaojie Wang; Hanbo Chen; Yurong Gao; Jun Meng; Zhongyuan Han; Lukas Van Zwieten; Yi He; Caibin Li; Gerard Cornelissen; Hailong Wang (Biochar)
Abstract Biochar is a promising technology for carbon storage and greenhouse gas (GHG) reduction, but optimizing it is challenging due to the complexity of natural systems. Machine learning (ML) and natural language processing (NLP) offer solutions through enhanced data analysis and pattern recognition, ushering in a new era of biochar research. Graphical Abstract